Assessing the Impact of the 4R Nutrient Management on Nitrogen Use Efficiency in Corn - Pedro Morinigo; Dorivar A. Ruiz Diaz (Kansas Agricultural Experiment Station Research Reports, 2023)
Determining the best management practices for nitrogen (N) fertilizer application to corn is crucial to achieving the objectives of the 4R of nutrient stewardship. Although producers have a wide range of options regarding N fertilization, identifying the right rate, source, placement, and timing (4R) can significantly impact productivity and nitrogen use efficiency. Our objectives were to evaluate the nitrogen agronomic efficiency (NAE), and the corn grain yields as affected by different rates, sources, placements, and timing methods of N fertilizer application under rainfed and irrigated conditions in Kansas. Two rainfed locations in Riley and Republic counties and two irrigated locations in Republic and Shawnee counties were established in 2021. Increasing rates from 0 to 180 lb N/a in 30-lb increments for rainfed locations and 0, 90, 120, 150, 180, 210, 240 lb N/a for irrigated locations were applied at planting, as broadcast urea. Additionally, five different N management treatments were applied at the same rate of 90 and 120 lb N/a for rainfed and irrigated locations, respectively. The nitrogen application significantly impacted the grain yield for both irrigated and rainfed locations. Applying N fertilizer as UAN coulter-injected at planting and SUPERU (Koch Agronomic Services, LLC) at side-dress V6 growth stage increased grain yield and AE across locations when compared to the baseline of urea broadcast at planting.
Keywords: Nitrogen; corn; soil fertility; 4R